Virtual Learning Environments In Faculties Of Education In Spain:Changes On Student Attitude - María Jesús Gallego Arrufat; Angel García-Beltrán (Universidad de Granada, 2010)
This paper presents some results of a R+D project entitled "e Learning system for Practical Training of University students in Education Faculties (ForELearn)", developed in Spain by the Universidad de Granada and the Universidad Politécnica de Madrid and funded by the Spanish Ministry of Education. In a first phase, through the use of AulaWeb Learning Management System, a set of adaptations and improvements of this software application have been done for the design and development of an experimental course of Practicum supervision. Next, the implementation of this course by means of a group of face to face and online seminars provides experimental data for the analysis and discussion about the point of view of users (preservice teachers) that have tracked their practice supervision with AulaWeb.